Parental Involvement in Follow – Up Learning Activities Relates to the Children’s English Language Skills Among Grade III pupils in the District of Castillejos, Division of Zambales, SY 2015 – 2016 - Corcoro, Lesley – Anne R. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The objective of the study was to ascertain the relationship between Grade III students' English language proficiency and parental participation in follow-up learning activities in the District of Castillejos, Division of Zambales, during the school year 2015–2016.   The questionnaire was the primary tool used to collect data from 150 parent respondents in this study, which used a descriptive research design. According to the survey, the average parent-respondent is a housekeeper, a high school graduate with an income below the poverty line, and a member of a household consisting of three to five people. It is determined that parental participation in follow-up learning activities is "sometimes practiced." According to the pre-test results, the students' English language proficiency "does not meet the 75% DepEd expectation." The post-test findings were excellent.   Additionally, the results indicated that there was no significant difference in parental participation when parent responses were categorized by profile, nor was there any difference in English language proficiency.   Additionally, a strong correlation between academic achievement and parental participation was discovered. However, there is significant difference on the pre- and post – test performance of the students.   Based on the summary of the investigation and conclusions arrived at, the researcher offered the following recommendations as to, have better academic performance, parents are encouraged to actively involved in making follow – up on the progress of their children; that the school should commit parents involvement especially those with children who are performing low in school;